Efeito dos tratamentos térmicos de revenimento simples e duplo na microestrutura e resistência à corrosão do aço inoxidável CA6NM - Ramos, Leonardo Bruno Honório (2023)
Martensitic stainless steels contain between 12-13% chromium, 2-5% nickel, 0,5-2,0% molybdenum and less than 0,06% carbon, classified according to ASTM (American Society for Testing and Materials). CA6NM martensitic stainless steels are applied to expand the technological advantages, associated with low costs, therefore they are widely used in services that require good mechanical resistance associated with corrosion resistance, mainly in equipment for oil extraction. The heat treatments used in CA6NM stainless steels are essential to obtain the desired mechanical properties and the control of heat treatment cycles can influence the microstructure and resistance to corrosion. Thus, this work aimed to evaluate the effect of quenching and quenching heat treatment. The steel was quenched by 2 hours at 1000°C and cooled in air. Then, the steel was tempered at 670°C for 10 hours and cooled in air, and subsequently a second tempering was performed at 600°C for 10 hours and cooled in air. Microstructural characterization, thermal analysis, hardness and microhardness measurements and polarization corrosion test were carried out in a 3,5% NaCl solution. Tempering heat treatments, both single and double, promoted a more defined and homogeneous microstructure, in addition to a microstructural refining aspect. The hardness values ​​after the single and double tempering treatment were within the ASTM A743 standard (max. 30HRC), with values ​​of 28 and 26 HRC, under the single and double tempering conditions, respectively, indicating that the heat treatments promoted relief of tension, reducing the hardness of the steel, but without significant differences between the treatments. Regarding corrosion resistance, there was an improvement in the electrochemical parameters in the tempered conditions in comparison to the steel in the crude melting condition, but there was no significant variation between the tempered conditions.